PENGARUH INTERGOVERNMENTAL REVENUE, KEKAYAAN PEMERINTAH DAERAH, DAN UMUR PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Pemerintah Kabupaten/Kota di Sulawesi Tengah) - Rafida, Rafida; Ridwan, Ridwan; Abdullah, Muhammad Ikbal; Yamin, Nina Yusnita (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study aims to analyze the effect of intergovernmental revenue, wealth of local government, and local government age to local government financial statement disclosure in Central Sulawesi. The analysis method used in this study is a multiple linear regression analysis. The results showed that intergovernmental revenue, local government wealth, and age of local government have a significant effect to the disclosure level of local government financial statements simultaneously. Intergovernmental revenue has a significant negative effect to the disclosure level of local government financial statements, while the wealth of local government and the age of local governments have no significant effect to the disclosure level of local government financial statements partially.